IDENTIFICATION OF FAMILI RUTACEAE IN THE SRIWIJAYA BOTANICAL GARDENS, OGAN ILIR DISTRICTS, SOUTH SUMATERA PROVINCE - Hamidi; YACHYA, ARIF; Nurokhman, Amin (Universitas PGRI Adi Buana Surabaya, 2023)
The Rutaceae famili is a citrus plant that is spread throughout Indonesia. These plants are rich with vitamin C, folate and fiber. Rutaceae members have not been well identified until now, especially in the Sriwijaya Botanical Gardens. This research aims to determine various species of plants in the Rutaceae family in the Sriwijaya Botanical Gardens. This research is a qualitative descriptive study. Data collection was carried out by direct exploring inside the Sriwijaya Botanical Gardens. The results found five species of the Rutaceae family, such as jeruk nipis or lime (Citrus aurantiifolia), jeruk kunci or calamansi (Citrus microcarpa), gongseng or orange berry (Glycosmis pentaphylla), sampang or euodia lunu-ankenda (Melicope lunu-ankenda) and kemuning or orange jasmine (Murraya paniculata).